An improved system for the measurement of blast waves in heterogenous environments tested on rapid minefield breaching - Du Plessis, Maximiljan (Stellenbosch : Stellenbosch University, 2025)
du Plessis, M. 2025. An improved system for the measurement of blast waves in heterogenous environments tested on rapid minefield breaching. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/ab4e81be-be03-4500-92b2-9807a8306d3d